Foreign institutional ownership and stock market liquidity: Evidence from Indonesia - Rhee, S. Ghon; Wang, Jianxin (Journal of Banking & Finance, 2009)
From January 2002 to August 2007, foreign institutions held almost 70% of the free-float value of the Indonesian equity market, or 41% of the total market capitalization. Over the same period, liquidity on the Jakarta Stock Exchange improved substantially with the average bid–ask spread more than halved and the average depth more than doubled. In this study we examine the Granger causality between foreign institutional ownership and liquidity, while controlling for persistence in foreign ownership and liquidity measures. We find that foreign holdings have a negative impact on future liquidity: a 10% increase in foreign institutional ownership in the current month is associated with approximately 2% increase in the bid–ask spread, 3% decrease in depth, and 4% rise in price sensitivity in the next month, challenging the view that foreign institutions enhance liquidity in small emerging markets. Our findings are consistent with the negative liquidity impact of institutional investor ownership in developed markets.